Teste do impulso cefálico (v-hit) em indivíduos com e sem diabetes mellitus tipo 1 - Marlon Bruno Nunes Ribeiro (2019)
Introduction: Some systemic diseases may interfere with the functioning of the vestibular system, including type 1 diabetes mellitus. Type 1 diabetes mellitus is an autoimmune disease characterized by progressive loss of beta-pancreatic cells, causing interruption of insulin production and metabolic imbalance. Studies show that the vestibular apparatus may be impaired in individuals with diabetes, even asymptomatic, which reveals the importance of a vestibular evaluation of this group. The assessment of vestibular function is mainly performed by measuring the response of the lateral semicircular canals after caloric stimulation. However, new complementary otoneurological exams have become useful tools for otoneurological diagnosis. Among these tests is the Video Head Impulse Test (v-HIT), a quick, practical and objective exam that evaluates each semicircular canal individually and at physiological frequency. Objective: To evaluate the effect of age on the vestibulo-ocular reflex gain through v-HIT in the group of individuals without self-reported otoneurological changes and the function of the semicircular canals of participants with and without type 1 diabetes mellitus through v-HIT . Methodology: A crosssectional, observational, analytical study performed with a convenience sample of 35 diabetic subjects and 100 subjects without diabetes and without selfreported neurotoneological alterations. All participants answered a questionnaire to confirm the absence of current and previous vestibular disorders, and were submitted to vestibular evaluation through v-HIT examination and meatoscopy. Participants with DM1 also underwent tympanometry and audiometry, considering as inclusion criteria individuals who presented type A typanometry and hearing within the normality or sensorineural loss patterns, ruling out any conductive loss. Results: This research resulted in two articles, the first article presented a sample of 90 participants without selfreported otoneurological alterations and a decrease in the gains of the posterior semicircular canals was observed with increasing age. The second article comprised a sample of 100 individuals with no self-reported otoneurological changes and diabetes, whereas the case group comprised 35 individuals with DM1; there was a decreased gain in the posterior and left anterior semicircular canals of the DM1 group when compared to the non-diabetic group. There was no difference in the presence of balloons between groups. Conclusion: There was a reduction of the gain of the posterior semicircular canals with the increase of the age in the individuals without self-reported otoneurological alterations. Participants with diabetes presented decreased gain in the posterior semicircular canals and in the left anterior canal when compared to the nondiabetes group. The averages of the semicircular canals gain of the nondiabetic group are in agreement with the literature.